Advances and Failures in Preventing Perinatal Human Immunodeficiency Virus Infection - Buchanan, Ann M. (American Society for Microbiology (ASM), 2009)
Summary: An estimated 2.5 million children are currently living with HIV, the vast majority as a result of mother-to-child transmission. Prevention of perinatal HIV infection has been immensely successful in developed countries. A comprehensive package of services, including maternal and infant antiretroviral therapy, elective cesarean section, and avoidance of breast-feeding, has resulted in transmission rates of less than 2%. However, in developing countries, access to such services is often not available, as demonstrated by the fact that the vast majority of children with HIV live in Africa. Over the past few years, many developing nations have made great strides in improving access to much-needed services. Notably, in eastern and southern Africa, the regions most affected by HIV, mother-to-child-transmission coverage rates for HIV-positive women increased from 11% in 2004 to 31% in 2006. These successes are deserving of recognition, while not losing sight of the fact that much remains to be done; currently, an estimated 75% of pregnant women worldwide have an unmet need for antiretroviral therapy. Further work is needed to determine the optimal strategy for reducing perinatal transmission among women in resource-poor settings, with a particular need for reduction of transmission via breast-feeding.